Emerging child competencies and personality pathology: toward a Developmental Cascade model of BPD. (February 2021) - Lyons-Ruth, Karlen; Brumariu, Laura E
Highlights: We discuss the tasks of each developmental period that need to be addressed in a developmentally grounded theory of BPD. We synthesize existing longitudinal and observational work within each developmental period, to build toward a Developmental Cascade Model for future work. We contrast trajectories toward BPD with those toward antisocial behavior, noting shared and divergent predictors, to address specificity. We note important future directions, including the need to assess type and timing of maltreatment and to integrate neurobiological markers in developmental models of BPD. Abstract : The guiding principle of this synthesis is to organize research on predictors of BPD features within a developmentally specific framework (e.g. infancy, preschool, middle childhood, adolescence). In addition, studies are prioritized that have longitudinal and observational components. On the basis of current literature, a Developmental Cascade Model of BPD is offered in which specific difficulties during one developmental period contribute to specific difficulties in a succeeding period, resulting in increasingly broad areas of dysregulation over time. Furthermore, to address specificity, we contrast trajectories toward BPD with trajectories toward antisocial behavior, noting shared and divergent predictors. The review highlights the importance of locating research findings in relation to the competencies and challenges of particular developmental periods when modelling developmental trajectories toward BPD.